Una adición para la flora de Chile: Eremocharis confinis I.M.Johnst. (Apiaceae) - Teillier, Sebastián (Gayana Botánica, 2010)
During an expedition to the Inka Trail at Socoroma, Parinacota Province, XV Region of Chile; about 3150 m altitude, we found a population of Eremocharis confinis I.M.Johnst. (Apiaceae-Umbelliferae), a new adding for the flora of Chile. That species was described by I.M. Johnston at neighboring Perú, at a locality named Candarave, at the Departamento de Tacna. With this found, Eremocharis had two species in Chile: the desertic-schrub E. fruticosa Phil. and the new altiplanic E. confinis.